Appealing to the base or to the moveable middle? Incumbents' partisan messaging before the 2016 U.S. congressional elections. Issue 4 (2nd October 2019) - Hemphill, Libby; Shapiro, Matthew A.
ABSTRACT: This paper examines partisan communications of incumbent members of Congress during the nine weeks leading up to the 2016 U.S. election. The central premise is rooted in the median voter theorem, which is coupled with theories of political activation and reinforcement, to show how politicians communicate in order to attract support from large swaths of the public. We analyze the partisanship of tweets posted by incumbents in Congress using mixed-effects models to examine the relationships between party, time, and race competitiveness on the degree of partisanship expressed by politicians. Our results reveal that Democrats and Republicans exhibited different partisanship signaling patterns in the weeks before the election. Specifically, Democrats decreased their partisanship, perhaps to appeal to the median voter, while Republicans stayed consistent in their partisanship, potentially using Twitter to activate and reinforce voters rather than to win them over.